Colfax Communities and a few more - Stanley, F. frey50 (Raton, New Mexico Coda Productions, 2006)
These facsimile reproductions present a small portion of F. Stanley's splendid research into the history of Northern New Mexico and, most importantly, its vibrant pioneering communities.
Keywords: The Capulin Story; The Farley Story; the Johnson Mesa Story; The Miami Story; the Otero Story; The Roy Story; The Wagon Mound Story; the Watrous Story; Wagon Mound; The Maxwell Story